Involvement of Oxidative Stress and Antioxidants in Modification of Cardiac Dysfunction Due to Ischemia-Reperfusion Injury - Dhalla, Naranjan S; Ostadal, Petr; Tappia, Paramjit S (Antioxidants (Basel, Switzerland), 2025)
Delayed reperfusion of the ischemic heart (I/R) is known to impair the recovery of cardiac function and produce a wide variety of myocardial defects, including ultrastructural damage, metabolic alterations, subcellular Ca2+-handling abnormalities, activation of proteases, and changes in cardiac gene expression. Although I/R injury has been reported to induce the formation of reactive oxygen species (ROS), inflammation, and intracellular Ca2+ overload, the generation of oxidative stress is considered to play a critical role in the development of cardiac dysfunction. Increases in the production of superoxide, hydroxyl radicals, and oxidants, such as hydrogen peroxide and hypochlorous acid, occur in hearts subjected to I/R injury. In fact, mitochondria are a major source of the excessive production of ROS in I/R hearts due to impairment in the electron transport system as well as activation of xanthine oxidase and NADPH oxidase. Nitric oxide synthase, mainly present in the endothelium, is also activated due to I/R injury, leading to the production of nitric oxide, which, upon combination with superoxide radicals, generates nitrosative stress. Alterations in cardiac function, sarcolemma, sarcoplasmic reticulum Ca2+-handling activities, mitochondrial oxidative phosphorylation, and protease activation due to I/R injury are simulated upon exposing the heart to the oxyradical-generating system (xanthine plus xanthine oxidase) or H2O2. On the other hand, the activation of endogenous antioxidants such as superoxide dismutase, catalase, glutathione peroxidase, and the concentration of a transcription factor (Nrf2), which modulates the expression of various endogenous antioxidants, is depressed due to I/R injury in hearts. Furthermore, pretreatment of hearts with antioxidants such as catalase plus superoxide dismutase, N-acetylcysteine, and mercaptopropionylglycerine has been observed to attenuate I/R-induced subcellular Ca2+ handling and changes in Ca2+-regulatory activities; additionally, it has been found to depress protease activation and improve the recovery of cardiac function. These observations indicate that oxidative stress is intimately involved in the pathological effects of I/R injury and different antioxidants attenuate I/R-induced subcellular alterations and improve the recovery of cardiac function. Thus, we are faced with the task of developing safe and effective antioxidants as well as agents for upregulating the expression of endogenous antioxidants for the therapy of I/R injury.
Keywords: subcellular defects; ischemia–reperfusion injury; cardiac dysfunction; oxidative stress; antioxidants; Ca2+-handling abnormalities